Anaesthetic management of large meningioma excision complicated by Takotsubo and posterior reversible encephalopathy. Issue 2 (2nd February 2022) - Santos, Sérgio; Castro, Mafalda; Raimundo, Ana; Ribeiro, Ana
Abstract : A 47-year-old woman with a history of a pulsatile headache, photophobia, dizziness and blurred vision was diagnosed with a massive expansive meningioma and proposed for surgical excision. During surgery, the patient began to show progressive haemodynamic instability with extreme hypotension and severe arrhythmia that only responded to epinephrine. With the continuity of haemodynamic instability, ST segment elevation and great amount of blood loss, the surgery was postponed. The follow-up brain CT scan showed evidence of posterior reversible encephalopathy syndrome and cardiac catheterisation diagnosed as Takotsubo syndrome. The patient remained sedated under aminergic support and was admitted to a cardiac intensive care unit. After clinic stabilisation, the patient underwent two more surgical procedures with special attention paid to monitoring haemodynamic stability, blood loss and cardiac output. After 70 days of admission, the patient was discharged with moderate visual impairment and follow-up consultations in neurosurgery and cardiology.